Triphenylphosphane Oxide Complexes of Lanthanide Nitrates: Polymorphs and Photophysics. Issue 11 (30th May 2018) - Barnes, Francis H.; Kelly, Andrew W.; Melzer, Henry; Patterson, Howard H.; Pike, Robert D.
Abstract : A series of mer ‐[ Ln (NO3 )3 (Ph3 PO)3 ] complexes were prepared from Ln (NO3 )3 · x H2 O and Ph3 PO in chloroform ( Ln = La, Nd, Sm, Eu, Gd, Tb, Dy, and Er). The La and Nd complexes were 0.25 CHCl3 solvates, whereas the others were solvent‐free. The identical reaction using Yb(NO3 )3 · x H2 O produced the unique salt trans ‐[Yb(NO3 )2 (Ph3 PO)4 ][Yb(NO3 )4 (Ph3 PO)]· Et2 O. All nitrate ions in all complexes are η 2 ‐chelating. A comparison of the various [ Ln (NO3 )3 (Ph3 PO)3 ] structures, including those in the literature, reveals at least four common polymorphs, each of which is represented by isomorphic structures of multiple Ln ions. Luminescence of mer ‐[ Ln (NO3 )3 (Ph3 PO)3 ] ( Ln = Y, La, Nd, Sm, Eu, Gd, Tb, and Dy), trans ‐[Yb(NO3 )2 (Ph3 PO)4 ][Yb(NO3 )4 (Ph3 PO)] and Ph3 PO assignments are reported. Latva's empirical rule allows for the antenna effect, in which energy is transferred from the triplet state of the Ph3 PO ligand, to occur only for Tb 3+ . Excitation via Ph3 PO results in strong green luminescence for Tb 3+ having twice the intensity as that which results from direct excitation of the f‐f transitions. Abstract :